Low Cost Reversible Signed Converter - Haitham Abbood, Wisam (Journal of Engineering and Sustainable Development, 2009)
The image compression required signed data that has a symmetric about zero to improve the efficiency of the compression. The unsigned images will convert to signed images using 1’complement (1’C) converter or 2’complement (2’C) converter. The converter (1’C or 2’C) has two problems first is the transform is not reversible because the overlap in the last two values for 1’C or the first two values for 2’C. Second it is high cost for the general converter. The proposed method is a hybrid method between 1’C and 2’C make the overlap in the middle two values, that will give a reversible conversion and it has a very low cost for the general converter.